Lucy's Dance - Vanasse, Deb (Book collections on Project MUSE., 2011)
A charming children's book about the return of traditional dancing to one Yup'ik village, Lucy's Dance tells the story of a little girl who is determined to help her grandfather demonstrate for the people of the town the beauty and complexity of old-style dancing. Threaded through the story are accounts of Yup'ik arts such as drumming, singing, and storytelling through dance, all brought to life with beautiful, full-color illustrations.